Model Ancaman Kapal Selam Terhadap Keamanan Maritim Indonesia Menggunakan Non-Cooperative Game Theory - Hadi, Yoos Suryono; Khusaini, Mohammad; Fadli, Mohammad; Kusumaningrum, Adi (Rekayasa, 2023)
Liberalization of the defense industry in Western countries and fundamental changes in military doctrine have created a variety of sophisticated weaponry used by developed countries. The aim of war today is no longer to control enemy territory, but to rely on sophisticated weaponry to achieve certain goals. This journal highlights the complex threats emanating from submarine military modernization in the Asia Pacific and its impact on Indonesia's maritime security. This research uses the AHP method to look for the biggest submarine threats, then uses game theory to play out the strategies of the countries that have the biggest threats. This research examines threats from neighboring countries that have advanced submarines and formulates appropriate strategies to maintain Indonesia's maritime security. The research results show that Australia is the country with the highest submarine threat level in the region, followed by China and Singapore. Malaysia has a lower threat level. In facing the threat of nuclear submarines from Australia, Indonesia must design an effective maritime defense strategy by considering diplomacy, regional cooperation, increasing defense capabilities and comprehensive policy planning. This is important to maintain national security and stability in the era of increasingly developing submarine military modernization in the Indo-Pacific region.